The allergic eye: recommendations about pharmacotherapy and recent therapeutic agents. Issue 4 (August 2020) - Kimchi, Nofar; Bielory, Leonard
Abstract : Purpose of review: Ocular allergies affect an estimated 40% of the population, 98% of which are because of allergic conjunctivitis. With the current advent of both repurposed drugs for ocular allergies, as well as novel drugs and methods of administration, there is a need for an updated review of current available medications. A clear characterization of each treatment will ultimately allow treating physicians to restore patients' quality of life and decrease burden of disease. Recent findings: Currently, there are a number of reformulated antihistamines, with cetrizine being the most recent ophthalmic solution available. Nevertheless, there is ongoing research in the field of immunotherapy, steroids, flavonoids, cannabis, and drug-delivery systems. Summary: Although dual-activity agents remain the keystone for treatment, newer drugs and drug-delivery systems offer other novel directions for delivering appropriate relief with minimal adverse effects.